2012
DOI: 10.1111/j.1570-7458.2012.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of the Asiatic citrus psyllid, Diaphorina citri, on healthy and huanglongbing‐infected citrus

Abstract: Diaphorina citri Kuwayama (Hemiptera: Sternorrhyncha: Psyllidae) is a vector of huanglongbing, a disease of citrus that in Asia is caused by ‘Candidatus Liberibacter asiaticus’ (α‐Proteobacteria) (Las). Acquisition of Las by D. citri appears to be variable, and this variability may be due to the suitability of the host plants and their tissues for acquisition. Therefore, this study aimed to determine the effect of symptom severity of the disease on the feeding behaviour of D. citri. Use of an electrical penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 47 publications
6
80
2
5
Order By: Relevance
“…The piercing-sucking mouth parts of ACP adults and their salivary sheaths have been studied [16], [17], but those of nymphs have not been studied so far. Also, the feeding behavior of ACP adults, but not nymphs, has been studied with electrical penetration graphs (EPG) [16], [18]. ACP adults were found to ingest sap mainly from the phloem sieve elements, although occasionally they also appear to ingest sap from xylem vessels [16], [18].…”
Section: Introductionmentioning
confidence: 99%
“…The piercing-sucking mouth parts of ACP adults and their salivary sheaths have been studied [16], [17], but those of nymphs have not been studied so far. Also, the feeding behavior of ACP adults, but not nymphs, has been studied with electrical penetration graphs (EPG) [16], [18]. ACP adults were found to ingest sap mainly from the phloem sieve elements, although occasionally they also appear to ingest sap from xylem vessels [16], [18].…”
Section: Introductionmentioning
confidence: 99%
“…These components provide information on stylet tip position in specific plant tissues, time spent at each location, and stylet activity (Tjallingii, 1985). The EPG waveforms of psyllids are reported for D. citri (Bonani et al, 2010;Cen et al, 2012b), B. cockerelli (Butler et al, 2012;Pearson et al, 2014;Sandanayaka et al, 2014;Mustafa et al, 2015), C. pyri L. (Civolani et al, 2011) and Psylla pyricola Förster (Ullman & McLean, 1988). Comparison by EPGs waveforms of the probing behaviours of males and females of B. trigonica in carrot has been recently reported (Antolínez et al, 2017a) and the characterization of the electrical penetration graphs (Antolínez et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, after the initial attraction to the odors produced by Las-infected young shoots, D. citri might move to uninfected ones. The leathered surfaces of Las-infected citrus plants was not found to have any effect on choice of host plants by Asian citrus psyllids, although psyllids spent more time on Las-infected plants because of the longer time needed to penetrate the parenchyma and reach the phloem (Cen et al, 2012). Inoue et al (2009) found that a large proportion (88%) of D. citri adults contained the bacterium (Las) after an access period of 24 h. The movement of D. citri adults infected with Las can facilitate the spread of the pathogen.…”
Section: Discussionmentioning
confidence: 85%